Formas de interação e formas de visibilidade no site da PUC-SP: em busca dos valores da produção de conhecimento - Malagutti, Ana Maria Longhi (2010)
The research proposed in this masters research lists itself as a descriptive and interpretative study of the ways the PUC-SP website brings visibility or not to it s target audience the values of academic research which is one of the productions developed at the university. The problematic of this dissertation is how it s present on the website and with what visibility the construction of valuable set of actions of the academic research developed at the university that qualifies with an identity of academic excellence in the Brazilian educational context. The data characterizing the production of knowledge of PUC-SP enlisted on the website were raised and based on an outline of topics that articulating institutional research in the university's main website, on levels of graduate and postgraduate degrees, and in two Post graduate and two undergraduate courses, which were collected between January and August 2010, they were analyzed and interpreted. The semiotic theory developed around A. J. Greimas, in particular, the Socio-semiotics of E. Landowski, constituted the theoretical and methodological approaches employed for description and interpretation of how the construction of PUC-SP is to be seen from the semantic and syntactic investments that chooses to characterize it. The websites were analyzed as discursive organizations that bring its structure the simulacra of the sender and recipient and through these pictures that they put into circulation in their interactive processes both images and interactions were analyzed according to the interactional schemes that E. Landowski developed from the postulates of narrative grammar of AJ Greimas and his associates. Special attention was directed to the analysis of figurative themes, from procedures enounced and from the organization of the configurating values that we call institutional picture. From this perspective we examine the types of contacts and contracts established between sender and recipient (thruth-contract the thruth say of the site and a trusted agreement - the way the site makes the recipient believe) and we observe that the discursive construction of the website has yet much to develop to produce a type of interactive network, specially to target mechanisms of dialogue with the audience that is complex in its segmentation, as the website proved to be addressing several audiences: faculty, staff and students already in the institution and those interested in becoming a student. The correlation between the regimen of interactions and regimen of visibility allowed us to determine that the institutional research at PUC-SP which is the grater value of it s organizational identity does not have a successful delivery not even in interaction, nor figurative exploitation and the plasticity of the syncretic level of expression of the website. The postulation of the generative trajectory of meaning in the examination of discursive manifestations as an object of signification and communication was thus the course of our testing of hypotheses. With prospective intention, from the state of search visibility of PUC-SP on the website, we propose considerations for its axiological incorporation to be more effective for the construction of an adequate visibility to this university's knowledge production